Survei periodik kepuasan layanan Perpustakaan IPDN kampus NTB tahun 2022 - I Wayan Wijanaraga; Agussalim Mad Arab (UIN Mataram, 2023)
Users are the subject and at the same time the object of library services, because users feel the most about whether the services they receive are able to meet their needs for the necessary scientific information. Therefore, the level of user satisfaction needs to be measured periodically using various methods, one of which is through surveys. The purpose of this study was to determine the level of user satisfaction for the NTB IPDN Campus for the 2022 period in the form of a User Satisfaction Index. The method used is descriptive qualitative with secondary data sources from searches or literature studies of relevant previous research results for comparison. Study results. The User Satisfaction Index for Library services in 2022 has increased by an average of 4%, when compared to the 2021 period. The highest increase in service elements is the element of service fees/tariffs with a difference of 231 points or an increase of 7%. While the element of service with the smallest difference is found in the element of service procedures by 27 points or 1%. Listening to all the service elements (9 elements), all of them experienced an increase in user satisfaction from the 2021 survey when compared to the 2022 survey results. The conclusion of this study is that the User Satisfaction Index for library services IPDN Campus NTB in 2022 obtained an average value for all service elements of 3.326 or converted with user satisfaction index interval values entered in the performance of service units in the GOOD category